2014
DOI: 10.2319/011014-38.1
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of tooth development stage of the maxillary anterior teeth before and after secondary alveolar bone graft: Unilateral cleft lip and alveolus vs unilateral cleft lip and palate

Abstract: SABG performed at approximately 9 years of age might increase tooth development speed of MXC in patients with UCLP compared with patients with UCLA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 13 publications
1
8
0
Order By: Relevance
“…All subjects in both groups showed normal root length of MXC on the cleft side compared to the noncleft side. This was similar to the study by Park et al 15 that reported that, although the UCLP group showed delayed development of MXC on the cleft side compared to the noncleft side one month before SABG, the MXC on the cleft side developed faster than that on the noncleft side after SABG, eventually resulting in no difference in the Nolla stage.…”
Section: Parameters At T2 (Table 5)supporting
confidence: 91%
“…All subjects in both groups showed normal root length of MXC on the cleft side compared to the noncleft side. This was similar to the study by Park et al 15 that reported that, although the UCLP group showed delayed development of MXC on the cleft side compared to the noncleft side one month before SABG, the MXC on the cleft side developed faster than that on the noncleft side after SABG, eventually resulting in no difference in the Nolla stage.…”
Section: Parameters At T2 (Table 5)supporting
confidence: 91%
“…The 32-year-old woman reported a traumatic injury involving her teeth when she was 6 years old, age when the front incisor are in eruption route [6] and Nolla stage 7 (complete crown and 1/3 of the root's development) [12]. On the other hand, the 8-year-old girl's mother said that the white mass appeared after 3 months her daughter had been through iliac crest bone craft for oronasal fistula repair.…”
Section: Discussionmentioning
confidence: 99%
“…We did not have access to previous CT scans or other radiographic images to determine whether or not trauma and maxilla crafting were the main causes of tooth ectopic eruption. Despite the lack of previous CT scans or other radiographic images, the patients' age suggests that Nolla stage in both of them could be classified as 7 or 8 [12], which could be a facilitating factor for the tooth displacement.…”
Section: Discussionmentioning
confidence: 99%
“…Group C involves 16- and 17- year-old patients (Table 1 ). The development stages of the teeth were assessed according to Nolla calcification stage 10 and classified as Nolla stage ≤6 or ≥7.…”
Section: Methodsmentioning
confidence: 99%